Uterine carcinosarcoma-induced pulmonary tumor thrombotic microangiopathy: A case report - Takashi Hibiya; Shigeaki Umeda; Koji Okudela; Mitsuko Furuya; Shoji Yamanaka; Kenichi Ohashi (Elsevier, 2018)
Pulmonary tumor thrombotic microangiopathy (PTTM) is a rare complication of cancer. It is histologically characterized by fibrocellular intimal proliferation in small pulmonary arteries and arterioles in patients with metastatic carcinoma. It is most frequently caused by adenocarcinoma. We report a case of PTTM caused by uterine carcinosarcoma in a 62-year-old female, who exhibited reductions in blood pressure and oxygen saturation. This is the first case report about uterine carcinosarcoma-induced PTTM. Histologically, the primary uterine carcinosarcoma included serous carcinoma and homologous sarcoma components. Many tumor emboli were observed across large regions of both lungs. PTTM was found in the lower lobes. Interestingly, the embolized tumor cells were all derived from the adenocarcinoma component. Immunohistologically, the primary carcinosarcomaexhibited weak positivity for tissue factor (TF), but was negativefor vascular endothelial growth factor-A (VEGF-A). The PTTM tumor cells were positive for TF and weakly positive for VEGF-A. This case suggests that any tumor containing adenocarcinoma can cause PTTM, and immunostaining of the primary tumor might be worthless for determining whether PTTM will develop. PTTM should always be considered during the differential diagnosis of dyspnea in patients with adenocarcinoma. Keywords: Pulmonary tumor thrombotic microangiopathy, Pulmonary tumor embolism, Vascular endothelial growth factor, Tissue factor, Uterine carcinosarcoma